In-Vitro Evaluation of the Acaricidal Efficacy of Polyherbal Aqueous Formulation against Rhipicephalus microplus - Yadav, Yogita; Choudhary, Nidhi S; Mehta, Hemant; Agrawal, Vivek; Dangi, Rakesh (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
A total of 140 fully engorged adult female ticks were used for the present study. Out of this, 20 ticks were used for performing larval packet test (LPT) and remaining 120 ticks were used in Adult immersion test(AIT). In AIT, polyherbal formulation exhibited notable inhibition of oviposition and adult tick mortality. Furthermore, In LPT, it demonstrated increased effectiveness on R. microplus larvae from the Mhow region, resulting in a higher mean percent mortality. These findings highlight the promising potential of the polyherbal formulation as a potent acaricidal agent in tick control strategies.